2024
DOI: 10.1182/blood.2023021815
|View full text |Cite
|
Sign up to set email alerts
|

The remission status of AML patients after allo-HCT is associated with a distinct single-cell bone marrow T-cell signature

Anna Mathioudaki,
Xizhe Wang,
David Sedloev
et al.

Abstract: Acute myeloid leukemia (AML) is a hematologic malignancy for which allogeneic stem cell transplantation (alloSCT) often remains the only curative therapeutic approach. However, incapability of T cells to recognize and eliminate residual leukemia stem cells (LSCs) might lead to an insufficient graft-versus-leukemia (GvL) effect and relapse. Here, we performed single-cell RNA-sequencing on bone marrow (BM) T lymphocytes and CD34+ cells of six AML patients 100 days after alloSCT to identify T cell signatures asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The prognostic efficiency of 14TGS was further validated in other AML cohorts, and 14TGS demonstrated robust predictive value. Interestingly, one recent study published in Blood reported a distinct single-cell T-cell signature associated with stem cell transplantation outcome in AML patients; one of the included genes was GPR56 , a biomarker of alloreactive CD8+ T cells ( 55 ). This further suggested that cluster_2 T cells are a novel subset that has different phenotypes and mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic efficiency of 14TGS was further validated in other AML cohorts, and 14TGS demonstrated robust predictive value. Interestingly, one recent study published in Blood reported a distinct single-cell T-cell signature associated with stem cell transplantation outcome in AML patients; one of the included genes was GPR56 , a biomarker of alloreactive CD8+ T cells ( 55 ). This further suggested that cluster_2 T cells are a novel subset that has different phenotypes and mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…TR supervised computational analysis. AM helped with the set-up of the SCENIC pipeline 14,15,41 and run initial SCENIC analyses. JZ supervised the set-up of the SCENIC pipeline 14,15,41 .…”
Section: Authorshipmentioning
confidence: 99%
“…AM helped with the set-up of the SCENIC pipeline 14,15,41 and run initial SCENIC analyses. JZ supervised the set-up of the SCENIC pipeline 14,15,41 . MS, GE, CE provided patients samples and data for the analyses.…”
Section: Authorshipmentioning
confidence: 99%